PRINCIPLES OF STUDYING LIVER MORPHOLOGY IN EXPERIMENTAL DIABETIC FOOT SYNDROME - Ergashev Ulugbek Yusufjanovich; Zokhirov Adkhamjon Rafiqovich; Abdusalomov Behzod Alisher ugli; Gafurov Behzod Tohirovich (Scholar Express Journals, 2023)
Study of the treatment of alloxan diabetes in the liver, taking into account pathomorphological aspects in the complex treatment of experimental diabetic foot syndrome
Keywords: experimental model of diabetic foot; experimental animals; diabetes mellitus